Structure-preserving approach to multi-port dynamic compact models of nonlinear heat conduction. Issue 12 (December 2015) - Codecasa, Lorenzo; d׳Alessandro, Vincenzo; Magnani, Alessandro; Rinaldi, Niccolò
Abstract: A novel approach for constructing multi-port dynamic compact thermal models of nonlinear heat diffusion in electronic components is presented, extending a technique previously conceived for the one-port case. The approach allows achieving high levels of accuracy even for small state–space dimensions of the model. It is also very efficient since it requires the solutions to a few linear heat diffusion problems in the frequency domain. The multi-port compact models exhibit structure similar to the one-port counterparts and can be used to accurately approximate not only the junction temperatures, but also the whole space–time temperature distribution within the electronic components.